The Apostrophic Impasse: Diacritical Remarks on the Stories of International Law, Legal Decolonial Genealogy and Antony Anghie’s Historiography - Hendrix, Britt L.A.Q. (Haadiya) (AUC Knowledge Fountain, 2022)
The (hi)stories of international law have strengthened the tentacles of coloniality in the legal regime as they continue to taunt the precarious lifeworlds of people, our planet and social imaginaries of an otherwise. The flow of coloniality has similarly rematerialized in decolonial legal theories and the postcolonial historiographical accounts of international law. I intend to demonstrate this colonial revival in the groundbreaking text of Antony Anghie Imperialism, Sovereignty and the Creation of International Law (2005) which challenged the (hi)stories of traditional jurisprudence. The latter was not necessarily a rejection nor negation of Western thought, because I argue that postcolonial historiography and decolonial legal theory, in general, have equally returned to multiple temporal and spatial concepts developed in the intellectual colonial habitus and took a recourse to early-European doctrines and ushered in modern modes of thinking. The general purpose of this dissertation is to identify the colonial ontologies in temporal and spatial structures embedded in the legal decolonial discourse in order to recognize the serious limitations of the current critical legal theories that have come to function at the heart of the legal progress theology and the ever-becoming coloniality of law as it is situated in the ethnographic sensorium (João Biehl & Peter Locke, 2017) of our social dimension. Throughout my writing I identify the inability to delink from colonial ontologies in critical legal theory as “the apostrophic impasse” and subsequently opt for different ways of reading into this term to become sensible and legible subjects under the chassis of international law.